answersLogoWhite

0


Best Answer

2a-5

User Avatar

Wiki User

โˆ™ 2009-05-13 03:10:41
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

๐Ÿ““
Create a Study Guide

Add your answer:

Earn +20 pts
Q: 9a plus 8 minus 2a minus 3 minus 5a?
Write your answer...
Submit
Related questions

Simplify 9a plus 8 minus 2a minus 3 minus 5a?

2a+5


2a plus 5a plus 9a equals?

2a+5a+9a = 16a


What is 9a plus 8-2a-3-5a?

9a +8 -2a -3 -5a = 2a +5


4a squared minus 9a plus 5?

4a2 - 9a + 5 = 4a2 - 4a -5a + 5 = 4a(a - 1) - 5(a - 1) = (4a - 5)(a - 1)


Simplify 7a plus 2a plus 1?

9a + 1


What is 9a plus 3b-11a-4b?

9a + 3b - 11a - 4b = -2a -b


What is a plus 3a plus 5a equals 180?

a + 3a + 5a = 180 9a =180 a = 20


What is 9a-a-a-a-a?

It is the same as: 9a -4a = 5a


9a plus 15 equals 7a plus 9?

Collect like terms: 9a -7a = 9 - 15, ie 2a = -6, so a = -3


9a plus 2 equals 4a-18?

so 5a = -20 making a = -4


What is 2a - 9a?

It is: -7a when simplified


How do you solve a squared minus 4 over 2 plus 6a times 3 plus 9a over a squared plus 5a plus 6?

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)


How do you solve this equation 4a-2.1 equals 9a plus 5.4?

4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5


How do you Factor the trinomial 2a squared - 9a-18?

(a - 6)(2a + 3)


What is 9a minus 8a simplified?

9a - 8a = a


How do you factor 81a2 plus 36a plus 4?

(9a + 2)(9a + 2)


If 5a 4a-1 equals 9a-4 what is the method used to get that answer?

Because of limitations with the question software, some symbols cannot be rendered, so we don't know what operation there is between the 5a and the 4a-1. Assuming a plus sign produces an inconsistent equation. But if we assume a / (slash) for division, we get a quadratic equation that produces some reasonable roots, so here's what I think the question is: Can you solve the following equation for a: 5a/(4a-1) = 9a-4 ? Yes you can! Multiply both sides of the equation by 4a-1. This gives you: 5a = (9a-4)(4a-1) Expand the right side, which gives you 5a = 36a2 -9a -16a + 4 Subtract 5a from both sides and group similar terms: 0 = 36a2 -30a + 4 Now, use the quadratic formula to solve for a(left to the student): a1 = 2/3; a2 = 1/6


What is the factor of a2 plus 9a plus 20?

a2+9a+20 = (a+4)(a+5) when factored


A plus 3a plus 5a equals 180?

Gathering like terms together, this can be rewritten: 9a = 180 Dividing both sides of the equation by 9: a = 20


What is the answer to 9a plus 5?

There is nothing you can do to 9a + 5 without knowing the value of a.


What is the answer to a plus b plus c equals 180 b equals 3a c equals 5a?

a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100


-14 plus 9a equals 38?

-14 + 9a = 389a = 52a = 52/9 or 5.78


What is 3a plus 4b plus 6a plus 3b in algebra?

9a + 7b *remember to look and understand the letters!*


What is the answer to 11a-a-a?

9a. You take 11 a's: a a a a a a a a a a a and then take away two (minus a, minus a): a a a a a a a a a X X


What is 9a plus 21 equals?

9a+21 3(3a+7)